Pengembangan LKPD Berbasis PjBL dalam Pembelajaran Matematika untuk Meningkatkan Sikap Tanggung Jawab Kelas V Sekolah Dasar - Florentinie Crisik Ating; Bistari Bistari; Asmayani Salimi; Siti Halidjah; Budiman Tampubolon (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2023)
This study aims to produce worksheet products for students based on Project Based Learning in learning mathematics to improve the attitude of learning responsibility in class V School decent basis. The research method used is research and development (RnD) by adapting the 10-step development model of Borg and Gall. The data sources for this research were the results of the validation of 2 validators, the results of the product test questionnaire of students and the results of the questionnaire on students' learning responsibility attitudes. The data collection technique for this research is a questionnaire validator validation, student product test questionnaire, learning responsibility attitude questionnaire and documentation on LKPD used by teachers. The results showed that during the process of developing Project Based Learning worksheets to increase the attitude of learning responsibility it was carried out in 7 steps, namely preliminary studies and information gathering, planning, initial product development, initial trials, product revisions, field trials and revisions to field trials. The feasibility level of LKPD based on the assessment of design experts is 96% in the very good category and the assessment from material experts is 94.52% in the very good category. The response of students' learning responsibility attitudes increased based on the first questionnaire of 89.77% with very good category and the second questionnaire was 93.57% in the very good category.